OP0224 RESULTS OF A PHASE 2 STUDY OF RG6125, AN ANTI-CADHERIN-11 MONOCLONAL ANTIBODY, IN RHEUMATOID ARTHRITIS PATIENTS WITH AN INADEQUATE RESPONSE TO ANTI-TNFALPHA THERAPY. (June 2019) - Finch, Rebecca; Sostelly, Alexandre; Sue-Ling, Kim; Blaeuer, Angela; Duchateau-Nguyen, Guillemette; Ukarma, Lidia; Petry, Claire; Ravva, Patanjali; Villiger, Peter; Junker, Uwe
Abstract : Background: Cadherin-11 is expressed on fibroblasts in joints of RA patients and augments local fibroblast–mediated inflammation, pannus formation and tissue invasion (1). RG6125 is a novel humanized monoclonal antibody directed against Cadherin-11. Objectives: To assess the safety, tolerability and efficacy of RG6125 as adjunctive treatment in patients with moderately to severely active RA and an inadequate response to anti-TNF-α therapy. Methods: The Phase 2 study was conducted as a multicenter, randomized, double-blind, placebo-controlled study. Patients were randomly assigned (2:1) to receive 810 mg of RG6125 or placebo by IV infusion. In the treatment period, patients received RG6125 or placebo IV infusions twice every two weeks and then monthly for a total of 4 dose administrations up to Week 12. The primary efficacy endpoint was the proportion of patients with ACR50 response at Week 12. Results: Demographics: 109 patients were randomized (98 female) to either placebo (N=37) or RG6125 (N=72) and were included in the efficacy analysis population. 107 patients were included in the safety analysis population (37 placebo, 70 RG6125). The median age was 55 years (22 – 78), and median RA disease duration was 12.4 years (1.0 – 42.4). Efficacy: Overall, there was little to no difference between RG6125 and placebo arms in the primary and secondary efficacy assessments (Table 1). Safety: More frequent musculoskeletal/connective tissue (14.3% vs. 8.1%) and gastrointestinal adverse events (12.9% vs. 8.1%) were noted on RG6125 compared to placebo, respectively. Two serious AEs were noted, one on RG6125 (intervertebral disc protrusion) and one on placebo (bacterial arthritis). No deaths occurred during the study. PK/PD: Pharmacokinetics of RG6125 appears linear at the dose range tested. There was no significant relationship identified between exposure groups, defined by Cavg, and the efficacy endpoints at week 12. The kinetics of continuous endpoints was not significantly different across the exposure groups. Non-responder imputation used for missing ACR responses. LOCF used for missing SJC/TJC. For ACR missing CRP has been imputed with ESR if available. No imputation for other missing components. No imputation for missing DAS28, CDAI, SDAI, HAQ-DI or MRI RAMRIS scores. * ANCOVA adjusted for baseline score and prior anti-TNFα therapy duration. MRI RAMRIS score is combination of the wrist and 1-5 MCP joints, and are exploratory endpoints. Conclusion: RG6125 was well tolerated with only mild to moderate AEs. RG6125 did not show a discernible treatment effect in RA patients in combination with anti-TNFα-blockers over placebo. Reference: [1] Lee DM, et al. Science 2007;315:1006-10. Disclosure of Interests: Rebecca Finch Shareholder of: Roche, Employee of: Roche, Alexandre Sostelly Shareholder of: Roche, Employee of: Roche, Kim Sue-Ling Shareholder of: Roche, Employee of: Roche, Angela Blaeuer Shareholder of: Roche, Employee of: Roche, Guillemette Duchateau-Nguyen Shareholder of: Roche, Employee of: Roche, Lidia Ukarma Shareholder of: Roche, Employee of: Roche, Claire Petry Shareholder of: Roche, Employee of: Roche, Patanjali Ravva Shareholder of: Roche, Employee of: Roche, Peter Villiger: None declared, Uwe Junker Shareholder of: Roche, Employee of: Roche